Spiral metal tube multi-roller bending springback prediction model based on dynamic deformation enhancement analysis. (1st November 2022) - Wang, Le; Wang, Zili; Zhang, Shuyou; Lin, Yaochen; Fu, Mengyu; Sun, Chang
Graphical abstract: Highlights: A prediction method of technological springback of spiral tube considering strain rate and relative twisting angle is established. The effects of feeding velocity, base circle radius, and lead angle on the springback results of the spiral tube are revealed. It is found that the variation of strain rate and relative twisting angle considering technological or geometrical parameters is a decisive factor to change the springback results. Abstract: The spiral metal tube has well stability manufactured by multi-roller bending (MRB) equipment owing to its curvature and torsion characteristics, while the springback is difficult to be alleviated concurrently. The effects of strain rate and relative twisting angle determined by process factors on springback cannot be ignored as well as the material and geometrical characteristics in MRB. In this paper, a novel theoretical model of the springback prediction of the spiral tube is established under the Frenet frame based on Johnson-Cook (JC) model and power hardening model. The concept of dynamic deformation enhancement analysis is proposed to clarify the impact of rate dependence on springback response. Taking the AISI 316L spiral tube as an example, the accuracy of the proposed theoretical model is verified by explicit finite element (FE) analysis and bending experiment. In the deviation analysis, the prediction deviation of the theoretical model is 1.72 %, which is closer to the experiment result than the FE analysis. The springback behavior of the spiral tube considering the variations of feeding velocity, base circle radius, and lead angle in the MRB process is studied. The elastic recovery of the spiral tube is characterized by the increase of the spiral base circle radius and the decrease of the lead angle. The results show that the higher strain rate and relative twisting angle have an enhancement effect on the spiral tube and reduce the elastic recovery in low forming speed MRB process.